Do Performance Measurement Systems and Ethical Leadership Style Affect Sustainable Investment Decisions? An Experimental Evidence - Praningtyas, Elisabeth Ria Viana; Sholihin, Mahfud (The Indonesian Journal of Accounting Research, 2024)
Management accounting is expected to be one of the significant tools to tackle environmental and sustainability issues. This study aims to fill the gap in the empirical results about the effect of performance measurement systems that include financial and sustainability indicators, one element of management accounting, on sustainable investment decisions. Additionally, this study examines whether ethical leadership plays a prominent role in that relationship. This study used an experimental method with 67 students majoring in accounting as participants. The data was collected online, where requirements for conducting an experimental study were fulfilled. The results of this study support the hypothesis that managers will be more likely to make sustainable investment decisions when their performance is evaluated using financial and sustainability performance measurements compared to that of financial performance measurement alone. Additionally, the effect is higher when their top managers perform high ethical leadership. The paper fills the gap in the literature about the effect of performance measurement and reward systems (PMRS) on sustainable investment decisions. This paper specifically gives direction for the business on how to react and take action amidst the sustainability era.